Forward Modeling Reveals Multidecadal Trends in Cambial Kinetics and Phenology at Treeline - Tumajer, Jan; Kašpar, Jakub; Kuželová, Hana; Shishov, Vladimir V.; Tychkov, Ivan I.; Popkova, Margarita I.; Vaganov, Eugene A.; Treml, Václav (Frontiers in Plant Science, 2021)
Significant alterations of cambial activity might be expected due to climate warming, leading to growing season extension and higher growth rates especially in cold-limited forests. However, assessment of climate-change-driven trends in intra-annual wood formation suffers from the lack of direct observations with a timespan exceeding a few years. We used the Vaganov-Shashkin process-based model to: (i) simulate daily-resolved numbers of cambial and differentiating cells; and (ii) develop chronologies of the onset and termination of specific phases of cambial phenology during 1961-2017.We also determined the dominant climatic factor limiting cambial activity for each day. To asses intra-annual model validity, we used eight years of direct xylogenesis monitoring from the treeline region of the Krkonoše Mts. (Czech Republic). The model exhibits high validity in case of spring phenological phases and a seasonal dynamics of tracheid production, but its precision declines for estimates of autumn phenological phases and growing season duration. The simulations reveal an increasing trend in the number of tracheids produced by cambium each year by 0.42 cells/year. Spring phenological phases (onset of cambial cell growth and tracheid enlargement) show significant shifts towards earlier occurrence in the year (for 0.28-0.34 days/year). In addition, there is a significant increase in simulated growth rates during entire growing season associated with the intra-annual redistribution of the dominant climatic controls over cambial activity. Results suggest that higher growth rates at treeline are driven by (i) temperature-stimulated intensification of spring cambial kinetics, and (ii) decoupling of summer growth rates from the limiting effect of low summer temperature due to higher frequency of climatically optimal days. Our results highlight that the cambial kinetics stimulation by increasing spring and summer temperatures and shifting spring phenology determine the recent growth trends of treeline ecosystems. Redistribution of individual climatic factors controlling cambial activity during the growing season questions the temporal stability of climatic signal of cold forest chronologies under ongoing climate change.